Energy Recovery from a Zipline Braking System via Regenerative Braking using Buck-Boost Converter - Magwili, Glenn V.; Adato, Ross Vincent F.; Belleza, Lio Anthony T.; Casanas, Patrick C.; Valdez, Herbert Joseph L.; Sauli, Zaliman (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This paper provides the study on the design, construction, and testing of a Regenerative Braking prototype, for zipline rides, that recovers energy upon its activation. The authors of this study wanted to address the energy crisis issue by providing other means for energy generation, which is the innovation of Regenerative Brake. The design of the prototype depends on the operating parameters of the chosen zipline ride. The elements used in the prototype are: geared dc motors, each coupled to the roller of the trolley; capacitors; Buck-Boost converter; and a lead-acid battery. The prototype works by having geared dc motors convert the kinetic energy from the rider to electrical energy. The generated electricity goes through the buck-boost converter to regulate the resulting voltage. This is done to meet the voltage requirement of the lead-acid battery before storing the regulated electricity. After recording the needed data, the resulting currents and battery charging times are averaged to help determine the energy generated. Resulting data showed it would take roughly two years to charge the 4Ah lead acid battery using the prototype for this study. Despite the minimal result, the prototype is proven to be capable of recovering energy from the zipline braking system. This implies that this study can now be an option for energy generation, instead of always resorting to construction of renewable- and coal-fired power plants.